2005
DOI: 10.1073/pnas.0509281102
|View full text |Cite
|
Sign up to set email alerts
|

Social relationships, sleep quality, and interleukin-6 in aging women

Abstract: This study examined the interplay of social engagement, sleep quality, and plasma levels of interleukin-6 (IL-6) in a sample of aging women (n ‫؍‬ 74, aged 61-90, M age ‫؍‬ 73.4). Social engagement was assessed by questionnaire, sleep was assessed by using the NightCap in-home sleep monitoring system and the Pittsburgh Sleep Quality Index, and blood samples were obtained for analysis of plasma levels of IL-6. Regarding subjective assessment, poorer sleep (higher scores on the Pittsburgh Sleep Quality Index) wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

14
148
0
4

Year Published

2008
2008
2018
2018

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 200 publications
(168 citation statements)
references
References 66 publications
(55 reference statements)
14
148
0
4
Order By: Relevance
“…However, the observed up-regulation of antibody synthesis genes in eudaimonic well-being is consistent with previous data showing enhanced antibody response to vaccination in people with high levels of well-being (48,49). The observed down-regulation of proinflammatory genes in eudaimonic wellbeing is also consistent with previous studies of protein biomarkers of inflammation and other cardiovascular risk factors (6,13,30,31,50,51). This study focuses on a one-time analysis of immune cell gene expression in a predominately white US sample, and replication of these findings in other populations with longitudinal assessment of well-being and biology will be required to gauge generality and consistency of these effects.…”
Section: Discussionsupporting
confidence: 91%
“…However, the observed up-regulation of antibody synthesis genes in eudaimonic well-being is consistent with previous data showing enhanced antibody response to vaccination in people with high levels of well-being (48,49). The observed down-regulation of proinflammatory genes in eudaimonic wellbeing is also consistent with previous studies of protein biomarkers of inflammation and other cardiovascular risk factors (6,13,30,31,50,51). This study focuses on a one-time analysis of immune cell gene expression in a predominately white US sample, and replication of these findings in other populations with longitudinal assessment of well-being and biology will be required to gauge generality and consistency of these effects.…”
Section: Discussionsupporting
confidence: 91%
“…For example, Liukkonen et al (2007) showed that elevated levels of CRP found in association with sleep disturbance (ie, self-reported problems sleeping) were greater than elevated levels associated with sedentary physical activity, low socioeconomic status, and tobacco smoking, but not with elevated body mass index. Likewise, Christian (Christian et al, 2011) found that self-reported poor sleep quality was correlated with CRP and IL-6 at a magnitude comparable to that between age and these markers of inflammation, but less than that found between BMI and CRP or IL-6; these latter findings are similar to those reported by Friedman et al (2005) Alternatively, the absolute change in levels of CRP or IL-6 with a healthy diet intervention (Neale et al, 2016), or aerobic exercise (Hayashino et al, 2014), is comparable to the absolute difference found in association with sleep disturbance.…”
Section: Naturalistic Sleep Disturbance and Systemic Markers Of Inflasupporting
confidence: 79%
“…However, these sex differences were only statistically significant for sleep disturbance predicting IL-6 and sleep duration continuously predicting CRP. Nevertheless, given evidence that women appear to be especially vulnerable to the effects of sleep loss on cellular inflammation (as noted above) (Irwin et al, , 2010, it is interesting to note that Suarez (2008) found that overall poor sleep quality was associated with increased inflammatory biomarkers, but only for women, similar to the findings of Friedman et al (2005) in older adults. Moreover, sex differences emerge in association with short sleep duration, as women, but not men, are more likely to show elevated levels of inflammation.…”
Section: Naturalistic Sleep Disturbance and Systemic Markers Of Inflasupporting
confidence: 63%
See 1 more Smart Citation
“…(Parati, et al, 2007;Vgontzas, et al, 2005) Considerably fewer studies, however, have employed non-clinical samples that are composed of individuals whose reported sleep disturbances do not reach clinical criteria. Although few in number, results have indicated that elevations in biomarkers of inflammation (Friedman, et al, 2005;McDade, et al, 2006) and coagulation (von Kanel, et al, 2006) as well as IR and psychosocial distress (Brummett, et al, 2006) are associated with individual differences in sleep quality and quantity.…”
Section: Introductionmentioning
confidence: 99%